2021
DOI: 10.1155/2021/1424675
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation on Antidiabetic Properties of Medicinal Plants from Myanmar

Abstract: Objectives. To explore the effective and safe medicines for treating diabetes. Methods. Hydroalcoholic extracts of 130 medicinal plants belonging to 66 families were evaluated using porcine pancreatic lipase (PPL) inhibition and glucose uptake methods together with a literature review. Results. The extracts of 22 species showed the PPL inhibition activity; 18 extracts of 15 species stimulated glucose uptake in 3T3-L1 adipocytes. Among them, Mansonia gagei J.R. Drumm., Mesua ferrea L., and Centella asiatica (L.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…In Brazil, C. lindenii was used for the treatment of stingray wounds and other pathogenic infections. There is no pharmacological or phytochemical research has been reported on C. lindenii 12 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Brazil, C. lindenii was used for the treatment of stingray wounds and other pathogenic infections. There is no pharmacological or phytochemical research has been reported on C. lindenii 12 .…”
Section: Discussionmentioning
confidence: 99%
“…The leaves, tubers, and other parts of C. lindenii were used therapeutically for stingray lesions in the regions of Brazil. However, no sufficient data has been found to reveal the presence of phytochemicals and pharmacological effects of C. lindenii in literature [ 12 ]. The underlying principle of the current research work is to explore the efficacy of organic extracts of C. lindenii with antiproliferative activity in response to the HepG2 (liver cancer) and normal HEK293T (human embryonic kidney 293T) cell lines.…”
Section: Introductionmentioning
confidence: 99%
“…Since it has been documented that medicinal plants of Myanmar have properties against diabetes, some species of this region were selected to investigate their effect on porcine pancreatic lipase inhibition and glucose uptake in 3T3-L1 adipocyte assays. The ethanolic extract of C. tiglium seeds showed the highest increase in glucose uptake at a concentration of 40 μg/mL, which could indicate a potential insulin-sensitizing effect [ 46 ].…”
Section: Resultsmentioning
confidence: 99%
“…The root of C. teeta has a berberine content of 6-7%, while the stem and leaf have lower concentrations of 2.00-3.00% and 1.00-1.97%, respectively. 34 Chen et al 61 investigated the alkaloid content of C. teeta collected from three different habitats in Yunnan Province, China. The alkaloid content of C. teeta varied among habitats, with the highest levels for jatrorrhizine (6.07-7.76 mg/g), columbamine (1.58-1.73 mg/g), epiberberine (0.36-0.66 mg/g), coptisine (14.93-17.81 mg/g), palmatine (4.61-5.24 mg/g), and berberine (78.99-84.85 mg/g).…”
Section: Phytochemicals/main Elementsmentioning
confidence: 99%